2015
DOI: 10.1007/s11259-015-9626-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manganese deficiency on the microstructure of proximal tibia and OPG/RANKL gene expression in chicks

Abstract: Manganese (Mn) deficiency can result in perosis in chicks, but the mechanism of Mn deficiency on tibia development remains poorly understood. Ninety one-day-old Arbor Acres male broiler chickens administered with control diet (60 mg Mn/kg) and Mn-deficient diets (40 mg Mn/kg, 8.7 mg Mn/kg) to investigate the effects of Mn deficiency on morphology of tibia and related signal transduction pathways in broiler chickens. At the age of 42 days, the bone trabecula, damaged osteoblasts and OPG/RANKL mRNA expression le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 27 publications
0
32
0
2
Order By: Relevance
“…TRAP and cathepsin K) directly involved in osteoclast functioning (Liu et al . ). In summary, Mn deficiency can lead to impaired formation of ECM, retardation of chondrocyte differentiation and increased osteoclast activity, thereby resulting in stunted growth and resorption of bones.…”
Section: Phosphorus – the Pivotal Point Of Investigationmentioning
confidence: 97%
“…TRAP and cathepsin K) directly involved in osteoclast functioning (Liu et al . ). In summary, Mn deficiency can lead to impaired formation of ECM, retardation of chondrocyte differentiation and increased osteoclast activity, thereby resulting in stunted growth and resorption of bones.…”
Section: Phosphorus – the Pivotal Point Of Investigationmentioning
confidence: 97%
“…Research conducted by Qin et al [ 22 ] indicates that Mn is a trace element necessary for the normal growth and development of bird embryos. Because Mn regulates the metabolism of hormones involved in bone metabolism [ 23 , 24 ], a diet low in Mn may increase the incidence of perosis in poultry and decrease the length of the tibia [ 25 , 26 ]. It has also been observed that a diet low in Mn may increase the production of thin-shelled eggs in laying hens [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The climbing pieces were removed, and glycerol ethanol was added dropwise. The staining effect was observed under a microscope and photographed under a 200x microscope [22]. The myocardial tissues were rapidly fixed in 10% formaldehyde for at least 24 h and embedded in paraffin for microscopic examination.…”
Section: Determination Of the Protein Expression Of The Proteinsmentioning
confidence: 99%